Rectal colonization with multidrug-resistant gram-negative bacteria in patients with hematological malignancies: a prospective study - TİGEN, ELİF; KORTEN, VOLKAN (TAYLOR & FRANCIS LTD, 2020)
Objectives To investigate the risk factors for rectal colonization with carbapenem-resistantEnterobacteriaceae(CRE) and extended-spectrum ss-lactamase-producingEnterobacteriaceae(ESBL-E) in hematological malignant patients with febrile neutropenia (FN); rate of rectal colonization and infection/colonization with CRE and ESBL-E; whether empirical treatment can be revised. Methods Adult patients receiving chemotherapy were included. Rectal swab cultures of patients were screened for CRE and ESBL-E using selective chromogenic agars. Results Fifty-seven FN episodes of 57 patients were studied. Rectal colonization rates were 40.4% (23/57) and 8.8% (5/57) for ESBL-E and CRE, respectively. ESBL-E bacteremia was diagnosed in 2 (8.6%) ESBL-E colonized patients, while CRE bacteremia was detected in 1 (20%) CRE colonized patient. Amikacin (100%) and carbapenem (93%) were the most effective antibiotics against gram-negative enteric bacteria. Beta-lactam usage within the last 3 months was a significant risk factor for ESBL-E colonization. Conclusions For the treatment of FN patients either colonized with ESBL-E or having significant risk factors for ESBL-E infection, aminoglycoside containing combinations may become an alternative to carbapenems due to their high sensitivity rates. When CRE colonized hematological cancer patients develop FN or if they are hemodynamically unstable, CRE covering empiric antibiotherapy should be preferred due to high mortality rates of CRE bacteremia.
Keywords: Febrile neutropenia; intestinal colonization; rectal carriage; multi-drug resistant; hematological malignancies; carbapenem-resistantEnterobacteriaceae; extended-spectrum ss-lactamase-producingEnterobacteriaceae; KLEBSIELLA-PNEUMONIAE; NEUTROPENIC PATIENTS; ESCHERICHIA-COLI; INFECTIONS; ENTEROBACTERIACEAE